MiRNA-190a-5p promotes primordial follicle hyperactivation by targeting PHLPP1 in premature ovarian failure - Zhang, Yuchi; Han, Dongwei; Yu, Xiaoyan; Shao, Xinyu; Zong, Chuju; Zhang, Manyu; Wang, Junzhi; Liang, Jingwen; Ge, Pengling (Frontiers in Genetics, 2022)
We previously screened 6 differentially expressed miRNAs in ovarian tissues of 4-vinylcyclohexene diepoxide (VCD)-treated premature ovarian failure (POF) model in SD rats, including miRNA-190a-5p, miRNA-98-5p, miRNA-29a-3p, miRNA-144-5p, miRNA-27b-3p, miRNA-151-5p. In this study, to investigate the mechanisms causing the onset of POF, we first identified miRNAs with earlier differential expression at consecutive time points in the VCD-treated rat POF model and explored the mechanisms by which the target miRNAs promote POF. The SD rats were injected VCD for 15 days to induce POF. Additionally, we collected rat blood and ovaries at the same time every day for 15 consecutive days and luteinizing hormone (LH), follicle-stimulating hormone (FSH), Anti-Mullerian hormone (AMH) and estradiol (E2) serum levels were detected by ELISA. Six miRNAs expression were measured in rat ovaries by qRT-PCR. Dual-luciferase reporter gene assays were employed to predict and verify the target gene (PHLPP1) of target miRNAs (miRNA-190a-5p). Western blot was examined to detect the expression levels of PHLPP1, AKT, p-AKT, FOXO3a, p-FOXO3a and LHR proteins on the target gene PHLPP1 and its participation in the primordial follicular hyperactivation-related pathways (AKT-FOXO3a and AKT-LH/LHR). During the VCD modeling POF rat ovaries, miRNA-190a-5p was the first to show significant differential expression, i.e., 6th of VCD treating, and PHLPP1 was verified to be a direct down-stream target of it. Starting from 6th of VCD treating, the more significant the up-regulation trend of miRNA-190a-5p expression, the more obvious the down-regulation trend of PHLPP1 and LHR mRNA and protein expression, accompanied by the more severe phosphorylation of AKT and FOXO3a proteins, thus continuously over-activating the rat primordial follicle to promote the development of POF. In conclusion, miRNA-190a-5p may become a potential biomarker for early screening of POF, and it can continuously hyperactivation primordial follicles in rats by targeting the expression of PHLPP1 and key proteins in the AKT-FOXO3a and AKT-LH/LHR pathways.